Complementary taxation of carbon emissions and local air pollution - Mathias Mier; Jacqueline Adelowo; Christoph Weissbart (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2022)
Current decarbonization policies neglect damages from local air pollutants. We analyze the trade-off between complementary taxation of carbon emissions and local air pollution. We quantify results for the European power market until 2050. Taxing only air pollution results in social cost of 5,890 billion exteuro and fosters nuclear deployment. Taxing only carbon yields social cost of 716 billion exteuro and promotes CCS deployment. Taxing both yields cost of 1,118 billion exteuro. Moderate carbon taxation can be complementary to a primary policy of air pollution abatement. On the contrary, a primary policy of decarbonization stands in trade-off with air pollution abatement in the long-term.
Keywords: C61; H21; H23; H43; L94; 330; Taxation; social cost; air pollution; carbon emission; externality; energy system model; power market model; decarbonization